Effects of Aqueous and Methanolic Extracts of Cichorium Intybus Seeds on Gentamicin Induced Nephrotoxicity in Rats - Muhammad Tahir , Noman Sadiq , Sameer Ahmed , Amanat Ali , Noor Nasir Rajpoot , Uzma Riaz (Journal of Islamic International Medical College, 2018)
Objective: To evaluate the effects of Aqueous and Methanolic extracts of Cichorium Intybus seeds on Gentamicin induced nephrotoxicity in rats. Study Design: Experimental Study Place and Duration of Study: Study was conducted from 15 January to 31 March 2017 at National Institute of Health Sciences (NIH) in collaboration with Riphah Institute of Pharmaceutical Sciences (RIPS). Materials and Methods: Forty healthy Sprague Dawly rats weighing 300-350gms were randomly divided in four groups with 10 rats each. Group A was the control group that received no medications. Group B was given Gentamicin 80mg/ kg body weight / day for 10 days intraperitoneally (IP). Group C was given Gentamicin 80mg/ kg body weight / day IP and Aqueous Extract of Cichorium Intybus seeds 500mg/kg body weight/ day through gavage tube for 10 days. Group D was given Gentamicin 80mg/ kg body weight / day IP and Methanolic Extract of Cichorium Intybus seeds 500mg/kg body weight / day through gavage tube for 10 days. Serum urea and creatinine were measured at day zero, 6, and 11. The values were compared within and between the groups. Results: Elevated levels of serum urea and creatinine were found in group B indicating renal damage. Whereas administration of Aqueous and Methanolic extracts of Cichorium Intybus seeds reduced the elevated levels of serum urea and creatinine in group C & D. However more reduction was produced in group C. Conclusion: Concomitant administration of Aqueous and Methanolic extracts of Cichorium Intybus seeds exerted nephroprotective effect on Gentamicin induced nephrotoxicity in rats. Aqueous extract produced greater protection as compared to Methanolic extract.